TYPES OF PERIPHERAL NEUROPATHY IN PARINKSON DISEASES (The Research of Medical Science Review, 2025)
The research investigates PN occurrence in PD patients by measuring SFN and LFN complaints. The study of 40 PD patients through cross-sectional analysis showed SFN affected 45% of patients while LFN affected 25% of patients and combined forms of neuropathy affected 30% of patients. Peripheral Neuropathy showed higher rates among advanced PD patients as 60% of patients at Stage 3-4 Hoehn and Yahr classification experienced it. Sensory impairments were worse in SFN patients among those with both SFN and LFN. The prevalence of LFN reached 25% for all patients evaluated. Research showed that neuropathy symptoms such as tingling sensations and burning pain appeared in 62.5% of the patient population. The diagnostic methods included both nerve conduction studies and skin biopsies which validated sensory deficiencies among patients with SFN and LFN. The study results underline the critical need for urgent detection and treatment of PD conditions because it leads to enhanced patient health results as well as life quality enhancements.